CLUSTER-BASED RETRIEVAL USING LANGUAGE MODELING APPROACH: AN EXPLANATION - Gloria Virginia (Universitas Kristen Duta Wacana, 2011)
Nowadays, one of the demands for computer system is capability to process textmd natural language automatically. Consequently, the development of algolithms that€nabl€ computers to do such task has been one of the great challenges. Hence, anymbstantial progress in this domain will have a strong impact on numeious applicationir.nging from information retrieval, information filtering, and intelligent agentiJo speechrcmgnition, machine translation, and human-machine interaction [ro].Information retrieval is a task to retrieve relevant documents in response to aqurr-s b1'measuring similarity between documents in repositories and the query. Inryaen-t !'ears, the meaning of the term 'similar' between documents and query has beender oped. At first, a document is judged similar with the query merely bised on lexicalnnrtching sf the word between documents and query. Now, the term 'similar' is expandedb 6e meening of the query. It means that the query is not necessarily expressed in the dment, to come up with thejudgment that a document is similar with the query.Tn_ this paper I'm going to explain how it can be done, that the query is notttrPt